The Dark Side of Disclosure : Evidence of Government Expropriation from Worldwide Firms - Liu, Tingting; Ullah, Barkat; Wei, Zuobao; Xu, Lixin Colin (World Bank, Washington, DC, 2015)
This paper studies the effects of voluntary accounting information disclosure through auditing on firm access to finance, exposure to corruption, and sales growth. Relying on a data set of more than 70,000 firms in 121 countries, the analysis finds that disclosure can be a double-edged sword. On the one hand, audited firms exhibit a slightly lower level of financial constraints than unaudited firms. On the other hand, audited firms face a significantly higher level of corruption obstacles. The net effects of voluntary information disclosure on firm growth are negative, which can largely be explained by the fact that most of the countries in the sample are developing countries where institutions are weak. The beneficial effect of disclosure increases as a country’s property rights protection improves. The qualitative results are robust to considerations of the endogeneity of auditing and to alternative measures of corruption and financial constraints. The findings reveal the dark side of voluntary information disclosure: exposing firms to government expropriation where institutions are weak.